Análise de propagação de trincas por fadiga em uma viga da estrutura de um forno de reaquecimento - Leonardo Carneiro Vianna Schettini (2016)
Fatigue crack is one of main problems in mechanical components and metallic structures. In this work fatigue cracks are analyzed in one of beams that is in charge of translation movement of the billet inside the reheating furnace, in order to support the plans of inspection and maintenance. The study is based on fracture mechanics, applying concepts about crack propagation on mechanical components submitted to fatigue. The methodology consists in the global-local analysis strategy to calculate the crack propagation and the life under fatigue which was divided in three steps. The first one corresponds to the global linear elastic analysis of the beam, considering absence of cracks, using the numerical finite elements method (FEM) by SOLIDWORKS software. This step enables the establishment of critical regions considering the work to be done and, therefore, most susceptible to cracks. In the second step, two different cracks are inserted in the global model obtained in the first step. Crack position is defined by the reality of the failures observed in the translation beam, this enables the threedimensional simulation model to be closer to reality. From these models, displacements are obtained from maximum and minimum loads. At the end, the third step corresponds to the modeling using boundary element method (BEM) to analyze cracks in three-dimensional bodies, applying FRANC3D software. The displacements found in the second step are applied as contour conditions in the local models created on FRANC3D. Results of this third step can be used to refine global analysis of the second step, in a continuous process of refining analysis. Results of a tensioned plate are presented, similarly to the model proposed by BORGES (2010). It was observed that the values obtained with numerical methods were similar to the ones obtained using the fundamentals of fracture mechanics, validating the proposed methodology. The local models, presenting different cracks, of a plate taken from the translation beam and of a piece of the translation beam, exposed to a cyclic loading, have proven feasible to estimate crack propagation on mechanical components, based on fundamentals of fracture mechanics. In order to calculate the life under fatigue defined by NBR-8800, the results obtained are consistent when compared to the results coming from the local models.